Mom Knows More than a Little Ghost: Children’s Attributions of Beliefs to God, the Living, and the Dead - Dawoon Jung; Euisun Kim; Sung-Ho Kim (Religions)
The growing body of research on children’s understanding of extraordinary minds has demonstrated that children believe in the persistence of mental functioning after death. However, beyond the continuity of mind, the supernatural conception of death often involves the concept of the disembodied mind, which transcends the constraints of the physical body, possessing supernatural mental capacities. The current study investigated whether children differentiate between a dead agent’s mind and ordinary minds in terms of their perceptual and information-updating capacities. In a location-change false-belief task, which involved a story of a mouse protagonist that was either eaten by an alligator or not, 4- to 6-year-old Korean children (N = 114) were asked about the mental states of the protagonist, an ordinary adult (mom), and God. The results showed (1) older children’s tendency to respond in a way that differentiated (the living) mom from the dead protagonist, (2) an increasing trend of differentiating God’s super-knowingness from ordinary minds with age, and (3) inconclusive evidence regarding children’s differential responses to the dead versus living protagonist. This study suggests that children are not predisposed to view dead agents as possessing a disembodied and supernatural mind, highlighting the importance of cultural learning in the development of such religious concepts.